1996
DOI: 10.1097/00005392-199611000-00049
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Renal Scintigraphy in the Evaluation of Spinal Cord Injury Patients with Presumed Urosepsis

Abstract: Nuclear medicine renal scanning is a valuable adjunct in the evaluation of sepsis and presumed urosepsis in the spinal cord injury population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Most of the currently available data is from the pediatric patient population. However, recent studies have shown encouraging results using renal scintigraphy in adults with spinal cord injury, a population in whom the localization of UTI may be difficult based on clinical grounds alone [39,40]. Finally, the role of MRI in the diagnosis of acute pyelonephritis has yet to be established.…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…Most of the currently available data is from the pediatric patient population. However, recent studies have shown encouraging results using renal scintigraphy in adults with spinal cord injury, a population in whom the localization of UTI may be difficult based on clinical grounds alone [39,40]. Finally, the role of MRI in the diagnosis of acute pyelonephritis has yet to be established.…”
Section: Diagnostic Imagingmentioning
confidence: 99%